INTERNALIZATION OF ISLAMIC CHARACTER EDUCATION THROUGH ISLAMIC RELIGIOUS EDUCATION LEARNING FOR MENTALLY DISABLED STUDENTS - Sigit Raharja (EL- Hayah, 2024)
Character education is the basis of education for every individual, including for children with special needs, namely mentally retarded children in special schools, which are important to be instilled and accustomed to from an early age. This study aims to examine the implementation and strategies in internalizing Islamic character for mentally retarded students at SLB Anugerah. The type of research conducted by the researcher uses a descriptive qualitative method. The data analysis used three activity paths, namely data reduction, data display, drawing conclusions. From the results of the data analysis, the following conclusions were obtained: first, internalization of Islamic character is carried out through a hidden curriculum from various activities carried out including through reciting the Koran, congregational prayer activities, learning to memorize letters and prayers, learning fairy tales, religious holiday activities. Second, the method applied is by exemplary behavior from the surrounding environment, namely teachers provide examples for mentally retarded children together, habituation and discipline such as consistent congregational prayer activities, rewards and punishments such as giving gifts that increase children's enthusiasm and giving educational punishments to improve their discipline, and giving advice (ma'uidzotul hasanah). Fourth: the media used is visualization by utilizing pictorial learning media, concrete audio visuals by prioritizing the characteristics and needs of each mentally retarded student. Keywords: Character, Islamic Education, Mentally Disabled Students